Evaluation of oxidation-Antioxidation in Female Rats induces with Dioxins - Kmosh, Safa Masser (American Journal of Biology and Natural Sciences, 2026)
Dioxins are harmful to both humans and animals because they are persistent and poisonous environmental contaminants. Examining how dioxin exposure affected the oxidation-antioxidation balance in female rats was the primary objective of this investigation. Two groups of female Wistar rats were studied: one that did not receive dioxin and one that did. As part of their 28-day treatment, the dioxin-exposed group took orally. The liver, kidneys, and ovaries were tested for oxidative stress markers, such as lipid peroxidation, and antioxidant enzyme activity. Lipid peroxidation and were found to be significantly increased in the target organs following dioxin exposure. The group exposed to dioxin also had markedly reduced activity of antioxidant enzymes including catalase, glutathione peroxidase, and superoxide dismutase. Additionally, rats exposed to dioxin had their expression of genes related to antioxidant defense systems downregulated. These results show that female rats are more susceptible to oxidative damage after dioxin exposure because it upsets the oxidation-antioxidation equilibrium. We require effective solutions to reduce the deleterious impacts of these persistent environmental contaminants, and the results give mechanistic insights into the possible reproductive and metabolic repercussions of dioxin toxicity.